PEMBELAJARAN ALQURAN DI SEKOLAH DASAR ISLAM TERPADU KOTA MEDAN - Syamsu Nahar, Mardianto, Abbas, (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2018)
Abstract: This study aims to determine; 1) Quran learning program in SD IT Siti Hajar, SD IT Al-Munadi, and SD IT Khairul Imam; 2) The implementation of the Qurâan learning that is applied in SDIT Siti Hajar, SDIT Al-Munadi, dan SD IT Khairul Imam; 3) Studentsâ ability in learning of Qurâan in SDIT Siti Hajar, SD IT Al-Munadi, and SD IT Khairul Imam. This study applied qualitative method. Thefindings of this study are; 1) Qurâan learning programs conducted at the research location are generallyallocated at the same time in the morning with classical patterns; 2) The implementation of Qurâanlearning which is done by SD IT has a variety of alternative methods, students who have not completediqra âgenerally use the Latin memorization method with a repetition system; 3) With daily routines,generally SD IT (Siti Hajar, Al-Munadi, Khairul Imam) is able to complete the specified target, such ascompleting iqra âbefore class 4 (four), the able (tartil) read the Qurâan for grades 5-6, and able tomemorize juz 30. Through this study, The researcher encouraged to give the Qurâan learning to theirchildren from the early age, in addition to their productive age (golden age) as well as the challenges ofthe times which is getters away from Islamic values.Kata Kunci: Home Schooling dan Pembelajaran